Bond Characteristics of High Strength Concrete with Recycled Aggregate and FRP Bar - Kim, S.H.; Hong, S.U. (Asian Journal of Chemistry, 2014)
In this study, to evaluate bond behaviour between high strength concrete with recycled aggregate and fiber reinforced polymer (FRP) bar, 36 specimens were manufactured using substitution rate of recycled aggregate, compressive strength of concrete, arrangement direction of CFRP or GFRP bar. Concrete cubes were manufactured by referring to the standards in KS F 2441, ASTM 234 and CAS-S802. Bond stress and slip of specimens did not show certain standards and bond stress had a decreasing trend with increase in substitution rate of recycled aggregate. Also for horizontal specimens with 30 % substitution rate of recycled aggregate, top specimen had higher bond strength than bottom specimen. For specimens with 100 % substitution rate of recycled aggregate, bottom specimen had higher bond strength than top specimen. This study suggests that the difference according to the settlement of an aggregate is not large.